The WTO: Theory and practice - Kyle Bagwell; Robert W. Staiger (World Trade Organization (WTO), 2009)
We consider the purpose and design of the World Trade Organization (WTO) and its predecessor, GATT. We review recent developments in the relevant theoretical and empirical literature. And we describe the GATT/WTO architecture and briefly trace its historical antecedents. We suggest that the existing literature provides a useful framework for understanding and interpreting central features of the design and practice of the GATT/WTO, and we identify key unresolved issues.
Keywords: 330; Internationale Organisation; Internationale Wirtschaftsbeziehungen; Handelsabkommen; Welt